Strategy to Increase Resilient and Competitive MSMEs and Youth Organization through Empowerment of Innovative Human Resources in Cilodong Sub-District, Depok City - Kholik, Jajang Roni Aunul; Mulyana, Rochtanu; Wirawan, Setia Teguh; Jayadi, Rahmat (Jurnal Pengabdian Masyarakat Bestari, 2024)
The purpose of this community service is to improve the business of MSMEs and the Youth Organization community to become strong, competitive, and sustainable businesses and organizations. The community service process carried out is in the form of a counseling seminar activity with a method in the form of providing counseling materials on management science from various perspectives/scientific concentrations which was held on October 5, 2024 at the Cilodong Sub-District Hall Building, Cilodong District, Depok City, West Java Province. The result of this activity is that MSME and Youth Organization business actors become more aware of various perspectives on management science that can be applied in their business and community operational activities, which is expected to be able to encourage innovation and adaptation of MSMEs and Youth Organization to change, so that it can increase operational efficiency, competitiveness, and long-term growth.